2016
DOI: 10.3389/fnins.2016.00310
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Autoimmune Disorders Associated with Streptococcal Infections and Tourette's Syndrome in Preclinical Studies

Abstract: Accumulating evidence suggests that Tourette's Syndrome (TS) – a multifactorial pediatric disorder characterized by the recurrent exhibition of motor tics and/or vocal utterances – can partly depend on immune dysregulation provoked by early repeated streptococcal infections. The natural and adaptive antibody-mediated reaction to streptococcus has been proposed to potentially turn into a pathological autoimmune response in vulnerable individuals. Specifically, in conditions of increased permeability of the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 168 publications
(280 reference statements)
1
15
0
Order By: Relevance
“…The altered integrity of the serotonergic system in WATER-GAS mice was supported by a reduced reactivity to the pharmacological challenge with DOI and further confirmed by significant reductions in 5-HT and 5HIAA concentrations in the striatum. Moreover, in accordance with the hypothesis that anti-GAS antibodies result in central inflammatory processes 14 , 28 , we detected inflammatory infiltrates and ramified microglia at the level of the rostral diencephalon in GAS mice, thus supporting a role for microglia in autoimmune basal ganglia disorders like TS, OCD and PANDAS in general 29 . One aspect that warrants consideration relates to the fact that our experiments have been conducted under animal facility rearing (AFR) conditions and not under specific pathogen free (SPF) conditions, which by definition guarantee a higher level of sterility.…”
Section: Discussionsupporting
confidence: 89%
“…The altered integrity of the serotonergic system in WATER-GAS mice was supported by a reduced reactivity to the pharmacological challenge with DOI and further confirmed by significant reductions in 5-HT and 5HIAA concentrations in the striatum. Moreover, in accordance with the hypothesis that anti-GAS antibodies result in central inflammatory processes 14 , 28 , we detected inflammatory infiltrates and ramified microglia at the level of the rostral diencephalon in GAS mice, thus supporting a role for microglia in autoimmune basal ganglia disorders like TS, OCD and PANDAS in general 29 . One aspect that warrants consideration relates to the fact that our experiments have been conducted under animal facility rearing (AFR) conditions and not under specific pathogen free (SPF) conditions, which by definition guarantee a higher level of sterility.…”
Section: Discussionsupporting
confidence: 89%
“…The validated translational mouse model of PANDAS, adopted in the present study, has been extensively characterized from a behavioural and biochemical point of view in our previous studies [18,19]. Consistently with the hypothesis of the infectious and autoimmune pathogenesis of PANDAS (see [71]), we reported that repeated exposures to GAS induce an antibody-mediated response (also confirmed in the present study) and behavioural alterations homologous to clinical symptoms observed in PANDAS (impaired sensorimotor gating, and abnormal repetitive and perseverative behaviours). The behavioural phenotypes exhibited by GAS mice represent the preclinical analogue of core clinical symptoms observed in PANDAS and obsessive-compulsive syndrome [11,72,73], and are useful for studying their neurobiological basis.…”
Section: Discussionmentioning
confidence: 58%
“…Sometimes the symptomatology may retrace the typical Tourette syndrome phenotype, at the point that precise differential diagnosis between the two forms is often difficult, and so leading some authors to consider the two conditions a different manifestation of the same disease. This pathogenetic hypothesis is nowadays limited by the lack of evidence regarding etiological causes of TS, nevertheless, a possible interaction has been observed by Spinello et al [19], who documented that after a repeated GABHS infection, an immune response was generated which was associated with neurological and behavioral phenotypes similar to Tourette syndrome. Considering the wide heterogeneity of clinical manifestations and the possibility of overlap with any other neuropsychiatric disturbance, reaching the diagnosis of PANS/PANDAS can represent a real clinical challenge, requiring the support of biochemical and laboratory assays, together with complementary instrumental surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Besides standard psychiatric treatments, an alternative therapy could include a treatment/ prevention approach consisting of antibiotics or tonsillectomy [19] to prevent the recurrence of GABHS infections.…”
Section: Discussionmentioning
confidence: 99%